Formulation of protein rich ready to mix food based on rice soya blend - Litty Andrews (Department of Home Science, College of Agriculture, 1997)
The present study on "Formulation of protein rich Ready To Mix based on rice and soya. blend", rice and soy flour were selected as basic ingredients. Other ingredients tried along with these were milk powder and wheat flour. Fifteen combinations were tried using these ingredients. The principles governing the selection of the proper combination of ingredients were protein quality, consistency, cost and overall acceptability. The combination of rice, soya, milk powder and wheat flour in a 20, 50, 20 and 10 per cent respectively got the highest score for all parameters selected. Acceptability of the mix was assessed with special reference to nutritional significance, organoleptic qualities, preference among consumer and physiological tolerance. The developed mix contained nutrient such as (Energy. protein. fibre, calcium, magnesium and zinc) in adequate amounts. Organoleptic qualities of the mix was assessed in the laboratory with the, selected panel of technical experts as judges and the mix was found to be acceptable. Preference test conducted among farm women revealed that most of the farm women (97%) preferred the mix. The physiological tolerance of the developed mix was assessed by conducting nitrogen balance studies among human volunteers. Children of